ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL TEOREMA PHYTAGORAS - Delia Khoerunnisa; Indah Puspita Sari (IKIP Siliwangi, 2021)
This study aims to describe the difficulties of students and find the cause of the difficulties faced by students in the Pythagorean theorem material in solving problems or questions about the material. Where the type of research used is descriptive research. The research of class IX from SMPN 2 Cipongkor for the academic year 2020-2021. Data collection techniques in this study were tests and documentation. The difficulties that are generally faced by students are difficulty in understanding the concept of the Pythagorean theorem, difficulty in understanding the problem and difficulty in answering a problem on the Pythagorean theorem. Good mastery of material concepts is able to bring students to produce good solutions as well. Understanding concepts and understanding in answering questions must be mastered by students to make it easier to work on the questions presented.